Segmental resection of the duodenum for gastrointestinal stromal tumor (GIST) - Mennigen, Rudolf (BioMed Central, 2008)
BACKGROUND: Gastrointestinal stromal tumors (GIST) are the most frequent mesenchymal tumors of the gastrointestinal tract. The biological appearance of these tumors reaches from small lesions with benign appearance to aggressive sarcomas. Only 3–5% of GISTs are localized in the duodenum. There is a controversy, if duodenal GISTs should be treated by a duodenopancreatectomy or by a limited resection of the duodenum. CASE PRESENTATION: A 29-year-old man presented with an acute upper gastrointestinal bleeding from a submucosal tumor located in the proximal part III of the duodenum, 3 cm distal of the papilla of Vater. After an emergency laparotomy with ligation of tumor-feeding vessels in a primary hospital, definitive surgical therapy was performed by partial resection of the duodenum with a duodenojejunostomy. Histology revealed a GIST with a diameter of 2.5 cm and <5 mitoses/50 high power fields, indicating a low risk of malignancy. Therefore no adjuvant therapy with Imatinib was initiated. CONCLUSION: GISTs of the duodenum are a rare cause of upper gastrointestinal bleeding. Partial resection of the duodenum is a warranted alternative to a duodenopancreatectomy, as this procedure has a lower operative morbidity, while providing comparable oncological results.